2007
DOI: 10.1021/jp074279i
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Discrimination of a Gemini-Type Surfactant with Rigid Spacer at the Air−Water Interface

Abstract: Spontaneous separation of chiral phases was observed in the monolayers of a racemate of gemini-type twin-tailed, twin-chiral amphiphiles, (2R,3R)-(+)-bis(decyloxy)succinic acid and (2S,3S)-(-)-bis(decyloxy)succinic acid. The pressure-area isotherms of the interfacial monolayers formed at the liquid-air interface, and the 2D lattice structures studied through surface probe measurements revealed that the racemate exhibits a homochiral discrimination of the enantiomers in two dimensions. An enantiomeric excess (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Shankar et al [17,18] reported similar isotherms for (2R,3R)-(? )-bis(decyloxy)succinic acid, (2S,3S)-(-)bis(decyloxy)succinic acid and (±)-bis(decyloxy)succinic acid, but there were no maximum on their isotherms.…”
Section: Surface Pressure-area (P-a) Isothermmentioning
confidence: 75%
See 3 more Smart Citations
“…Shankar et al [17,18] reported similar isotherms for (2R,3R)-(? )-bis(decyloxy)succinic acid, (2S,3S)-(-)bis(decyloxy)succinic acid and (±)-bis(decyloxy)succinic acid, but there were no maximum on their isotherms.…”
Section: Surface Pressure-area (P-a) Isothermmentioning
confidence: 75%
“…Furthermore, the stereochemistry at the point of attachment of spacer group would also be one of the important structural factors for the surface properties of gemini surfactants. In this decade, several studies on the correlation between the stereochemistry at the point of attachment of spacer group, physical properties and self-aggregation behavior of gemini surfactants have been reported [14][15][16][17][18][19][20][21], but more research is needed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a Gemini surfactant molecule, the spacer is the key structural element. The length [13], rigidity [10,14,15] and stereochemistry [16,17] of the spacer affect the selfassembly of Gemini surfactants. Once an adsorption film has been formed by a Gemini surfactant, the spacer is expected to affect the interfacial dilatational behaviour because the position of the spacer is close to the head group of the surfactant and is situated within the adsorption layer.…”
Section: Introductionmentioning
confidence: 99%